The spatial heterogeneity and dynamics of tourism-flow spillover effect: The role of high-speed train in China. Issue 2 (March 2022) - Zhou, Bo; Wen, Zhihong; Sutherland, Ian; Lee, Seul Ki
The existing literature has not fully explored the spatial heterogeneity and dynamics of spillover effects of tourism-flow patterns, and this article makes contributions to addressing this issue. Using spatial autoregressive models and comparing the results for the non-high-speed train (HST) era (2002–2006) and those for the HST era (2011–2015) of China, this article finds that in the HST era, the spillover effect of tourism flows from neighboring regions has changed from positive to negative. Moreover, in the HST era, the cities with HST services have significantly positive effects on for a particular city, while those cities without HST have negative effects. These results reveal the spatial heterogeneity and dynamics of the tourism-flow spillover. After evaluating the variation of other factors which potentially contribute to the change of spillover patterns, this study identifies that the HST service plays an important role in such changes. Finally, this article uses geographically weighted regressions to explore the spatial heterogeneity in an elaborative way.